2004
DOI: 10.1161/01.atv.0000145979.82184.9f
|View full text |Cite
|
Sign up to set email alerts
|

Severe Periodontitis Enhances Macrophage Activation via Increased Serum Lipopolysaccharide

Abstract: Objective-In periodontitis, overgrowth of Gram-negative bacteria and access of lipopolysaccharide (LPS) to circulation may activate macrophages leading to foam cell formation. We investigated whether periodontal treatment affects proatherogenic properties of low-density lipoprotein (LDL) and, thus, macrophage activation. Methods and Results-LDL was isolated and characterized before and after treatment from 30 systemically healthy patients with periodontitis. Production of cytokines and LDL cholesteryl ester (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 43 publications
(33 reference statements)
6
144
3
4
Order By: Relevance
“…Previous studies suggested that periodontal inflammation could influence general health through elevated blood concentration of LPS (20,27). On the other hand, the present periodontal inflammation model did not increase the serum LPS level.…”
Section: Control Groupcontrasting
confidence: 84%
“…Previous studies suggested that periodontal inflammation could influence general health through elevated blood concentration of LPS (20,27). On the other hand, the present periodontal inflammation model did not increase the serum LPS level.…”
Section: Control Groupcontrasting
confidence: 84%
“…In fact, recent studies of periodontitis in human subjects have shown a correlation between the area of inflammation in the oral cavity and macrophage cytokine production and LDL cholesteryl ester uptake. 32 These proatherogenic changes are thought to be mediated by increases in serum LPS during periodontal infection and have been postulated to augment the risk of vascular disease in affected individuals. 33 Another novel finding here is that ligands for other TLRs also induce macrophage aP2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…After periodontal therapy, the serum HDL, cholesterol levels were found to be increased and statistically significant. However, it is to be noted that HDL is beneficial to the host, as it considered as antiatherogenic lipoprotein because of its direct role in neutralizing lipopolysaccharides in circulation, protecting LDL against oxidation as well as its role in reverse cholesterol transport (Pussinen et al) [22].…”
Section: Discussionmentioning
confidence: 99%